2011
DOI: 10.1128/aem.05028-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation with a Saccharomyces cerevisiae Mannan Oligosaccharide on the Bacterial Community Structure of Broiler Cecal Contents

Abstract: This study investigated the effects of dietary supplementation with a prebiotic mannan oligosaccharide (MOS) on broiler performance, bacterial community structure, and phylogenetic populations of cecal contents. Bird performance data were collected, and cecal samples were extracted from randomly caught poults from each treatment group every 7 days from hatching to the age of 42 days. Weight gain, feed consumption, and feed efficiency ratios did not differ significantly between groups. Automated ribosomal inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 56 publications
1
30
1
1
Order By: Relevance
“…Previous studies involving MOS supplementation in poultry have been carried out in both research and clean facility settings and have demonstrated alterations of the bacterial community structure (13,34). Due to the highly variable nature of the avian and broiler microbiotas across different flocks and even between birds in a flock (25,35), there is concern that prebiotics and other supplements may be effective only under limited conditions and may never be usefully employed across the industry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies involving MOS supplementation in poultry have been carried out in both research and clean facility settings and have demonstrated alterations of the bacterial community structure (13,34). Due to the highly variable nature of the avian and broiler microbiotas across different flocks and even between birds in a flock (25,35), there is concern that prebiotics and other supplements may be effective only under limited conditions and may never be usefully employed across the industry.…”
Section: Resultsmentioning
confidence: 99%
“…This barcode-based primer approach allowed sequencing of multiple samples in a single sequencing run without the need for physical partitioning. The PCR conditions and reagents were similar to those described previously, and a standard concentration of 50 ng of cecal DNA was used in each reaction (13). The PCR products were purified using a High Pure PCR product purification kit (Roche, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the cell walls of SC, making up 15 to 25% of its dry weight, is mainly composed of glucan and mannoproteins, including mannan-oligosaccharide and β-glucan (Yalçinkaya et al, 2008). It was reported to improve immune response and modulate intestinal microflora in animals (Corrigan et al, 2011;Vervicka and Oliveira, 2013). As mentioned above, a mixture of BA and SC was used to assess the benefits of DFM supplementation in broiler diets.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the dose, supplementation with FOS and MOS decreased the density of Clostridium perfringens and E. coli in chickens (Kim et al, 2011). Moreover, MOS supplementation would alter the structure of the bacterial community of chickens (Corrigan et al, 2011). In rabbit, studies on the influence of prebiotics concerned mainly growth performance and caecal fermentation activity with contradictory results even for the same type of prebiotic (for review Falcao-e-Cunha et al, 2007).…”
Section: Influence Of Nutritionmentioning
confidence: 99%